Defining the relationship between clinical and immunological features of asthma - Al Zahrani, Yousef (2019)
Background: Asthma is a chronic inflammatory disease in children and adults that is caused by many factors. The most common respiratory symptoms associated with asthma are wheezing, shortness of breath, chest tightness, and coughing, which alter with the duration and severity of the disease. Furthermore, other comorbidities are associated with severe asthmatics patients, such as allergic rhinitis, hay fever, and non-allergic rhinitis. Asthma is increasingly prevalent and affects around 300 million people worldwide. Approximately 5-10% of the asthma population suffers from a more severe form of the disease and has frequent exacerbations. There is a need for better understanding of how asthma presents in different patients, which will allow for stratified medicine approaches.